Common carpetgrass (Axonopus fissifolius) control with POST herbicides. (June 2019) - Henry, Gerald; Johnston, Christopher; Hoyle, Jared; Straw, Chase; Tucker, Kevin
Abstract: Reductions in MSMA use for weed control in turfgrass systems may have led to increased common carpetgrass infestations. The objective of our research was to identify alternative POST herbicides for control of common carpetgrass using field and controlled-environment experiments. Field applications of MSMA (2.2 kg ai ha −1 ) and thiencarbazone + iodosulfuron + dicamba (TID) (0.171 kg ai ha −1 ) resulted in the greatest common carpetgrass control 8 wk after initial treatment (WAIT): 94% and 91%, respectively. Thiencarbazone + foramsulfuron + halosulfuron (TFH) (0.127 kg ai ha −1 ) applied in the field resulted in 77% control 8 WAIT, whereas all other treatments were ≤19% effective at 8 WAIT. All treatments resulted in greater common carpetgrass control when applied in the greenhouse. Applications of MSMA, TFH, and TID resulted in the highest common carpetgrass control in the greenhouse 8 WAIT: 94%, 94%, and 91%, respectively. Control with nicosulfuron (0.035 kg ai ha −1 ) and trifloxysulfuron (0.028 kg ai ha −1 ) (81% and 75%, respectively) was greater in the greenhouse than observed in the field 8 WAIT. Sequential applications of foramsulfuron (0.058 kg ai ha −1 ) resulted in only ≤11% common carpetgrass control 8 WAIT, regardless of application site. All herbicide treatments in the greenhouse resulted in reduced aboveground common carpetgrass biomass 8 WAIT compared to the nontreated control (12.9 g). Aboveground biomasses of common carpetgrass in response to MSMA, TID, TFH, nicosulfuron, and trifloxysulfuron were 1.6 to 2.1 g, regardless of treatment. Reduced efficacy of foramsulfuron was reflected in greater biomass (4.7 g) in response to treatments. Thiencarbazone + iodosulfuron + dicamba may be an alternative to MSMA for common carpetgrass control; however, long-term assessment may be warranted to evaluate treatment effectiveness. Further investigation into application timing may be necessary to enhance the efficacy of TFH for the control of common carpetgrass.